Current collector with composite structure, preparation method of current collector, electrode plate and lithium ion battery

By introducing oxygen-containing SP2 hybrid carbon material and silane coupling agent into the lithium-ion battery pole collector, the composite structure current collector is solved, and the thermal coating cannot take into account both thermal conductivity and adhesive ability, significantly improving the heat transfer and safety performance of the battery cell.

CN119812347APending Publication Date: 2025-04-11ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411950646.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery pole-piece collector current thermal conductivity coating cannot take into account both thermal conductivity and adhesiveness, resulting in uneven heat exposure of the pole-piece, increasing safety risks.

Method used

The composite structure current collector is adopted, which includes a current collector matrix, a thermally conductive coating and a current collector binder. The thermally conductive coating uses an SP2 hybrid carbon material containing oxygen groups, and the binder uses a silane coupling agent to bridge the current collector matrix and the thermally conductive coating through covalent bonds.

Benefits of technology

It improves the overall thermal conductivity of the electrode plate, enhances the heat transfer and safety performance of the battery cell, and avoids safety risks caused by local overheating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812347A_ABST
    Figure CN119812347A_ABST
Patent Text Reader

Abstract

The invention discloses a composite structure current collector and a preparation method thereof, an electrode plate and a lithium ion battery. According to the composite structure current collector provided by the invention, the heat conduction coating is additionally arranged on the substrate of the current collector, and the current collector substrate and the heat conduction coating are bridged by using a special micromolecule binder in a covalent bond manner, so that the overall heat conduction performance of the current collector is improved. An SP2 hybrid carbon material with an oxygen-containing group is used as a key material for improving the heat conduction capability of the current collector in the material in the heat conduction coating, so that the heat conduction and electrical conductivity are good, new impurities are not introduced into a battery system, and the matching degree with a conventional battery cell system is good; the binder comprises a silane coupling agent which is a multi-branch chain hydrolyzable ring-opening micromolecule and has a branch chain capable of reacting with a group on the carbon material or a current collector matrix to generate a covalent bond, the energy conduction capability can be enhanced through the covalent bond, the bond energy is high, and the cohesiveness is strong; in addition, the binder is a common material, and has the economic advantages of being environmentally friendly, low in price and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary battery materials, and in particular to a composite structure current collector and a preparation method thereof, an electrode sheet and a lithium ion battery. Background Art

[0002] Lithium-ion batteries are widely used in 3C, electric vehicles, power tools and other products due to their advantages such as high energy density, no memory effect, long cycle life, environmental friendliness, and adaptability to various environments. The assembly process of lithium-ion batteries mainly includes winding process and lamination process. Among them, the positive and negative electrodes of the wound lithium-ion battery are long strips. Under high-rate charging, due to the uneven current density in the electrode and the influence of the impedance of the electrode on the lithium insertion behavior, a large amount of heat that cannot be transferred in time will be generated, which will lead to uneven heating of the electrode. The battery cell may produce local overheating, thereby reducing the service life of the battery cell and increasing safety risks.

[0003] In the related art, in order to improve the thermal conductivity of the electrode current collector, a common method is to add a thermal conductive coating. However, the current methods of adding thermal conductive coatings are mostly mechanical coupling at the microscopic level of the material, the coating has poor adhesion, is easy to fall off, and there are gaps between the two phase interfaces; or, although a polymer material with excellent adhesion is used, its thermal diffusion coefficient is low, resulting in limited improvement in the overall thermal conductivity of the electrode.

[0004] Therefore, it is of great significance to solve the problem that the existing current collector thermal conductive coating cannot take into account both thermal conductivity and adhesion ability at the same time, and to provide a current collector with a thermal conductive coating that has good adhesion, is not easy to fall off, and can effectively improve the overall thermal conductivity of the electrode, thereby improving the heat transfer performance and safety performance of the battery cell. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a composite structure current collector and a preparation method thereof, an electrode sheet and a lithium ion battery, aiming to solve the problem that the existing electrode sheet current collector thermal conductive coating cannot take into account both thermal conductivity and bonding ability.

[0006] In a first aspect of the present invention, a composite structure current collector is provided, comprising: a current collector substrate, a thermal conductive coating and a current collector binder;

[0007] The composition material of the thermal conductive coating includes SP containing oxygen groups. 2 Hybrid carbon materials;

[0008] The current collector binder includes a silane coupling agent;

[0009] The current collector binder bridges the current collector substrate and the thermal conductive coating through covalent bonds.

[0010] The composite structure current collector according to the embodiment of the present invention has at least the following beneficial effects: the composite structure current collector provided by the present invention adds a coating layer, namely a thermal conductive coating layer, on the substrate of the current collector, and a special small molecule adhesive is used between the substrate of the current collector and the coating layer. The adhesive bridges the coating layer and the substrate of the current collector in the form of a covalent bond, thereby improving the overall thermal conductivity of the current collector. Among them, the material in the thermal conductive coating layer uses SP with oxygen-containing groups. 2 Hybrid carbon materials, as key materials to improve the thermal conductivity of current collectors; SP 2 Hybrid carbon materials have unpaired electrons, good thermal and electrical conductivity, and will not introduce new impurities into the battery system. When they have oxygen-containing groups, they can be better modified. Moreover, the thermal conductive material is an oxygen-containing carbon material, which has a good match with the conventional battery system and will not deteriorate the electrical performance of the battery due to the introduction of new impurities. The binder includes a silane coupling agent, which is a multi-branched hydrolyzed ring-opening small molecule with a branched chain that can react with the groups on the carbon material to form a covalent bond, which can enhance the energy conduction ability through the covalent bond. Not only that, the carbon-oxygen branched chain of the binder can also form a covalent bond with the current collector matrix, which has high bond energy and strong adhesion, and will not introduce new impurities into the system. In addition, the binder is a common material and has economic advantages such as environmental friendliness and low price.

[0011] The composite structure current collector of the present invention adopts the above-mentioned SP having oxygen-containing groups. 2 Hybrid carbon materials are used as materials in thermal conductive coatings, and multi-branched hydrolyzable ring-opening small molecule silane coupling agents are used as adhesives to improve the overall thermal conductivity of the current collector. The reaction mechanism is as follows: the siloxane side chain at one end of the silane coupling agent can be hydrolyzed to form silanols, which react with oxygen-containing groups on the surface of the current collector matrix to form covalent bonds, connecting the current collector matrix; the siloxane side chain at the other end is hydrolyzed to form silanols, which react with oxygen-containing groups on the surface of the current collector matrix to form covalent bonds, connecting the high thermal conductivity carbon materials. After the adhesive forms a covalent bond with the matrix or carbon material, energy can be quickly transferred between the two phase interfaces in the form of lattice vibration, thus having the advantages of high bonding strength and high thermal conductivity. Finally, the composite structure current collector after constructing the thermal conductive coating has the characteristics of high thermal conductivity and high electrical conductivity, which effectively improves the overall thermal conductivity of the electrode, thereby improving the heat transfer performance and safety performance of the battery cell. The local high temperature generated by the battery cell during high-rate charging can be quickly transferred to the surrounding area through the improved current collector, avoiding local high temperature affecting the safety performance of the battery cell.

[0012] In some embodiments of the present invention, the thermally conductive coating is present on both side surfaces of the current collector substrate, and the current collector binder bridges the current collector substrate and the thermally conductive coating through covalent bonds.

[0013] In some embodiments of the present invention, the oxygen-containing group SP 2 The hybrid carbon material includes at least one of carbon nanotubes, graphene oxide, or reduced graphene oxide, but is not limited thereto. The above materials all include oxygen functional groups, which can generate covalent bonds (Si-OC) after dehydration condensation with silanols, etc. At the same time, SP 2 Hybrid carbon materials have unpaired electrons, good thermal and electrical conductivity, and will not introduce new impurities into the battery system; when they have oxygen-containing groups, they can be better modified.

[0014] Preferably, the oxygen-containing group SP 2 The hybrid carbon material is reduced graphene oxide (rGO).

[0015] Preferably, the carbon nanotubes include multi-walled carbon nanotubes.

[0016] In some embodiments of the present invention, the general formula of the silane coupling agent is RSiX3, wherein R represents amino, mercaptovinyl, epoxy, chloropropyl, cyano, methacryloxy and other groups, which have strong reactivity with different base resins, and X represents a hydrolyzable group, such as halogen, alkoxy, acyloxy, etc. Therefore, the silane coupling agent can interact with both the hydroxyl group in the inorganic substance and the long molecular chain in the organic polymer, thereby coupling the two materials with different properties.

[0017] In some embodiments of the present invention, the silane coupling agent includes at least one of 3-glycidyloxypropylmethyldiethoxysilane (3-GPTS or γ-GPTS), 3-aminopropyltriethoxysilane (3-APTS or γ-APTS), but is not limited thereto. The above-mentioned silane coupling agent as an adhesive has a side chain that can react with a group on a carbon material or an oxygen-containing group on the surface of a substrate to generate a covalent bond. The covalent bond formed has high bond energy and strong adhesion. The ability to conduct energy can be enhanced through covalent bonds, and new impurities will not be introduced into the system. At the same time, the adhesive is a common material with economic advantages such as environmental friendliness and low price. Its connection mechanism is to generate a covalent bond with a substrate or a carbon material, which can quickly transfer energy between the two phase interfaces in the form of lattice vibration, and has the advantages of high bonding strength and high thermal conductivity.

[0018] Specifically, 3-glycidyloxypropylmethyldiethoxysilane (3-GPTS) is also known as γ-glycidyloxypropyltrimethylsilane (γ-GPTS), silane coupling agent KH-78, CAS: 2897-60-1, molecular formula C 11 H 24O4Si; 3-aminopropyltriethoxysilane (3-APTS) is also known as γ-aminopropyltriethoxysilane (γ-APTS), silane coupling agent KH-550, etc., CAS: 919-30-2, molecular formula C9H 23 NO3Si. Small molecule coupling agents with structures similar to the above compounds can achieve similar effects to the present invention and are also within the scope of the present invention.

[0019] In some embodiments of the present invention, the composite structure current collector is a composite structure negative electrode current collector, comprising: a current collector substrate, a thermal conductive coating and a current collector binder; the current collector substrate comprises at least one of copper foil and composite copper foil; the composition material of the thermal conductive coating comprises SP containing oxygen groups 2 Hybrid carbon material; the current collector binder includes a silane coupling agent; the current collector binder bridges the current collector matrix and the thermal conductive coating through a covalent bond.

[0020] Figure 1 The figure shows a schematic diagram of the structure of one embodiment of the composite structure negative electrode current collector of the present invention. In the figure, the wound battery cell includes a positive electrode, a negative electrode, a separator and other structures; the negative electrode current collector is a composite structure, including a negative electrode current collector matrix, a thermal conductive coating and a binder, and both sides of the negative electrode current collector matrix have SP with oxygen-containing groups. 2 The thermal conductive coating is formed by hybrid carbon materials, and the substrate and the coating are connected by a silane coupling agent. The negative electrode current collector substrate is copper foil, which serves as the carrier of the negative electrode material and the thermal conductive coating layer of the battery cell; the thermal conductive coating is SP containing oxygen groups. 2 Hybrid carbon materials, such as reduced graphene oxide (rGO) or multi-walled carbon nanotubes, are key materials for improving the thermal conductivity of negative electrode current collectors; binders are multi-branched small molecules that can be hydrolyzed and ring-opened, such as 3-glycidyloxypropylmethyldiethoxysilane (3-GPTS). The reaction mechanism can be understood as follows: the siloxane branch at one end of the binder can be hydrolyzed to form silanols, which dehydrate and condense with oxygen-containing groups on the surface of the negative electrode current collector matrix to form a covalent bond (Si-O-Cu), connecting the negative electrode current collector matrix; the siloxane branch at the other end of the binder is hydrolyzed to form silanols, which dehydrate and condense with oxygen-containing high thermal conductivity carbon materials to form a covalent bond (Si-OC), connecting the high thermal conductivity carbon materials. The reaction mechanism diagram is shown in the figure below. Figure 2 The reaction equation is as follows:

[0021] Binder hydrolysis: R-Si-(O-CH3)3+3H2O→3MeOH+RSi(OH)3

[0022] Dehydration condensation: RSi(OH)3+COOH-R-OH+Cu-OH→Cu-O-RSi(OH)-O-C+H2O

[0023] In some embodiments of the present invention, the composite structure current collector is a composite structure positive electrode current collector, comprising: a current collector substrate, a thermal conductive coating and a current collector binder; the current collector substrate comprises at least one of aluminum foil and composite aluminum foil; the composition material of the thermal conductive coating comprises SP containing oxygen groups 2 Hybrid carbon material; the current collector binder includes a silane coupling agent; the current collector binder bridges the current collector matrix and the thermal conductive coating through a covalent bond. The structure and reaction mechanism of the composite structure positive electrode current collector are similar to those of the composite structure negative electrode current collector, except that the covalent bond generated by the dehydration condensation of the silanol generated by the hydrolysis of the siloxane side chain in the composite structure positive electrode current collector and the oxygen-containing groups on the surface of the positive electrode current collector matrix is ​​(Si-O-Al).

[0024] In some embodiments of the present invention, the thickness of the current collector matrix is ​​6-16 μm. Specifically, the thickness of the current collector matrix can be 6-8 μm, 8-10 μm, 10-12 μm, 12-14 μm, 14-16 μm or other ranges.

[0025] In a second aspect of the present invention, a method for preparing the composite structure current collector is provided, comprising the steps of:

[0026] S100, adding a silane coupling agent to an alcohol solution, and stirring and reacting for a predetermined time to generate a silanol solution;

[0027] S200, oxygen-containing SP 2 After the hybrid carbon material is evenly dispersed in the solvent, the silanol solution is added and stirred for a predetermined reaction time to generate a silanol-modified SP 2 Hybrid carbon material solution;

[0028] S300, immersing the current collector matrix in the silanol-modified SP at a predetermined temperature 2 After reacting in the hybrid carbon material solution for a predetermined time of three, the solution is cured by light irradiation to obtain the composite structure current collector.

[0029] The preparation method of the composite structure current collector according to the embodiment of the present invention has at least the following beneficial effects: the preparation method provided by the present invention is not only simple in process, but also has non-harsh reaction conditions, is compatible with the preparation process of the original electrode sheet or battery cell, and has the potential for large-scale application.

[0030] In some embodiments of the present invention, the volume fraction of the silane coupling agent in the silanol solution is 2 (v / v)% to 5 (v / v)%, preferably 3 (v / v)%. The present invention uses a laser thermal conductivity meter to test the thermal diffusion coefficient of the composite structure current collector prepared with different volume fractions of silane coupling agents, and the test temperature ranges from 25°C to 150°C. Through testing, it is found that when the volume fraction of the silane coupling agent is between 2% and 5%, a current collector with a good thermal diffusion coefficient can be prepared, among which, when the volume fraction of the silane coupling agent is 3%, the thermal diffusion coefficient of the material prepared by the silanol solution is the best.

[0031] In some embodiments of the present invention, the alcohol solution includes at least one of methanol, ethanol, and ethylene glycol, preferably a methanol solution.

[0032] In some embodiments of the present invention, the predetermined time is 3 to 5 hours, preferably 4 hours.

[0033] In some embodiments of the present invention, the second predetermined time is 1 to 3 hours, preferably 2 hours.

[0034] In some embodiments of the present invention, the predetermined time three is 10 to 40 minutes, preferably 30 minutes. The present invention uses a laser thermal conductivity meter to test the thermal diffusion coefficient of the composite structure current collector prepared by different immersion times of the current collector matrix, and the test temperature ranges from 25°C to 150°C. Through testing, it is found that when the immersion time is between 10 and 40 minutes, a current collector with a good thermal diffusion coefficient can be prepared, among which, when the immersion time is 30 minutes, the thermal conductivity effect is the best.

[0035] In some embodiments of the present invention, the predetermined temperature is 10-40° C., preferably 30° C. The present invention uses a laser thermal conductivity meter to immerse the current collector matrix in silanol-modified SP at different temperatures. 2 The thermal diffusion coefficient of the composite structure current collector prepared in the hybrid carbon material solution was tested at a temperature ranging from 25°C to 150°C. The test found that a current collector with a good thermal diffusion coefficient can be prepared when the immersion temperature is between 10°C and 40°C, and the thermal conductivity is best when the immersion temperature is 30°C.

[0036] In some embodiments of the present invention, the oxygen-containing SP 2 The hybrid carbon material was evenly dispersed in pure water by ultrasonication.

[0037] In some embodiments of the present invention, infrared light irradiation is used for light curing.

[0038] In a specific embodiment of the present invention, the specific process of step S100 is:

[0039] S101, adding glycerol to a methanol aqueous solution having an alcohol:water ratio of 1:8 to 1:12, adjusting the pH to between 4 and 6, and stirring evenly, marking as solution I;

[0040] S102, preparing a mixed solution of a silane coupling agent and anhydrous methanol in a certain ratio, marked as solution II;

[0041] S103, slowly adding solution II into solution I in a certain ratio, stirring and reacting for 3 to 5 hours to generate a stable silanol solution.

[0042] In a third aspect of the present invention, an electrode sheet is provided, comprising: a composite structure current collector as described above or prepared by the preparation method as described above, and an active material layer coated on at least one side of the composite structure current collector.

[0043] Since the electrode sheet adopts all the technical solutions of the composite structure current collector of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment. That is, the electrode sheet obtains the composite structure current collector by introducing the thermal conductive coating and the current collector binder into the current collector matrix, and the current collector binder bridges the current collector matrix and the thermal conductive coating through covalent bonds, so that the composite structure current collector can take into account both thermal conductivity and bonding ability, and the thermal conductive coating has good adhesion and is not easy to fall off, which can effectively improve the overall thermal conductivity of the electrode sheet.

[0044] In some embodiments of the present invention, the electrode sheet is a negative electrode sheet, and the negative electrode sheet includes the composite structure negative electrode current collector and a negative electrode active material layer coated on at least one side of the composite structure negative electrode current collector.

[0045] In some specific embodiments of the present invention, the current collector matrix of the negative electrode sheet includes at least one of copper foil and composite copper foil.

[0046] In some specific embodiments of the present invention, the raw materials of the negative electrode active material layer include a negative electrode active material, a negative electrode conductive agent and a negative electrode binder.

[0047] In the present invention, the negative electrode active material includes a silicon-based material, which can be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites, silicon alloys, or a mixture of silicon negative electrode materials and other currently commonly used negative electrode active materials, wherein the other negative electrode active materials include but are not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; the tin-based material can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys.

[0048] The negative electrode conductive agent includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fibers, and conductive carbon black. The present invention has no special requirements for the negative electrode conductive agent, and any conventional conductive agent in the art can be used.

[0049] The negative electrode binder includes at least one of polyvinylidene fluoride (PVDF) binder, sodium carboxymethyl cellulose (CMC) binder, styrene butadiene rubber (SBR) or polyacrylate (PAA) binder. The present invention has no special requirements for the negative electrode binder, and any conventional binder in the art can be used.

[0050] In some embodiments of the present invention, the electrode sheet is a positive electrode sheet, and the positive electrode sheet includes the composite structure positive electrode collector and a positive electrode active material layer coated on at least one side of the composite structure positive electrode collector.

[0051] In some specific embodiments of the present invention, the current collector matrix of the positive electrode sheet includes at least one of aluminum foil and composite aluminum foil.

[0052] In some specific embodiments of the present invention, the raw materials of the positive electrode active material layer include a positive electrode active material, a positive electrode conductive agent and a positive electrode binder.

[0053] In the present invention, the positive electrode active material is a positive electrode active material commonly used in lithium ion batteries, including but not limited to a chemical formula such as Li x Ni h Co y M z O 2-d N d (wherein 0.95≤x≤1.2, h>0, y≥0, z≥0, and h+y+z=1, 0≤d≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive electrode active material may also be subjected to a modification treatment, and the method for modifying the positive electrode active material should be known to those skilled in the art. For example, the positive electrode active material may be modified by coating, doping, etc. The material used for the modification treatment may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc.

[0054] The positive electrode conductive agent includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fiber, and conductive carbon black. The present invention has no special requirements for the positive electrode conductive agent, and any conventional conductive agent in the art can be used.

[0055] The positive electrode binder includes at least one of polyvinylidene fluoride (PVDF) binder, sodium carboxymethyl cellulose (CMC) binder, styrene-butadiene rubber (SBR) or polyacrylate (PAA) binder. The present invention has no special requirements for the positive electrode binder, and any conventional binder in the art can be used.

[0056] A fourth aspect of the present invention provides a battery cell comprising the above-mentioned electrode sheet.

[0057] Since the battery cell adopts all the technical solutions of the electrode sheet of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment. That is, it solves the problem that the current collector thermal conductive coating cannot take into account both thermal conductivity and adhesion at the same time. The thermal conductive coating has good adhesion and is not easy to fall off. It can effectively improve the overall thermal conductivity of the electrode sheet, thereby improving the heat transfer performance and safety performance of the battery cell.

[0058] In some embodiments of the present invention, the battery cell includes the above-mentioned positive electrode sheet and / or negative electrode sheet.

[0059] In some embodiments of the present invention, the battery cell further includes a separator between the positive electrode sheet and the negative electrode sheet.

[0060] In some embodiments of the present invention, the diaphragm may be any material suitable for lithium-ion battery diaphragms in the art, for example, it may be a combination of one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fiber, etc. In actual production, the material and structure of the diaphragm are not strictly limited, for example, it may be a multi-layer structure formed by stacking the above materials, it may be a single-layer structure formed by mixing the above materials, or it may be a single-layer structure formed by a single material; as long as it can play the basic role of a diaphragm.

[0061] A fifth aspect of the present invention provides a lithium-ion battery comprising the above-mentioned battery cell.

[0062] Since the lithium-ion battery adopts all the technical solutions of the battery cell of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, that is, the heat transfer performance and safety performance of the battery are improved.

[0063] In some embodiments of the present invention, the lithium-ion battery further comprises an electrolyte, and the electrolyte infiltrates the positive electrode, the negative electrode and the separator. The electrolyte comprises an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DEC, DMC or EMC; it can also be a carboxylic acid ester, including PP, MA, EA, EP, etc. The additives include, but are not limited to, at least one of film-forming additives, conductive additives, flame retardant additives, overcharge prevention additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low temperature performance, and water-based safety additives.

[0064] In some embodiments of the present invention, the present invention further provides a secondary battery, including the above-mentioned battery cell. The battery cell provided by the present invention can be applied not only to the above-mentioned lithium-ion battery, but also to other secondary batteries, including sodium-ion batteries, potassium-ion batteries, etc., without any limitation here.

[0065] In a sixth aspect of the present invention, a use of the above-mentioned lithium-ion battery in an energy storage device, an electrical device or an electronic device is proposed. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0067] Figure 1 A schematic diagram of the structure of the composite structure negative electrode current collector provided by the present invention;

[0068] Figure 2 A schematic diagram of the reaction mechanism of the binder in the composite structure negative electrode current collector provided by the present invention bridging the current collector matrix and the thermal conductive coating through covalent bonds;

[0069] Figure 3 A schematic structural diagram of a finished battery cell according to Example 14 provided by the present invention;

[0070] Figure 4 A schematic diagram of thermal imaging test results of each sample provided by the present invention at different temperatures;

[0071] Figure 5 A schematic diagram of the test results of thermal diffusion coefficients of samples prepared with different γ-GPTS volume fractions provided by the present invention;

[0072] Figure 6 A schematic diagram of the test results of thermal diffusion coefficients of samples prepared at different γ-GPTS-rGO solution temperatures provided by the present invention;

[0073] Figure 7 This is a schematic diagram of the thermal diffusion coefficient test results of the samples prepared by immersing in the γ-GPTS-rGO solution for different times provided by the present invention. DETAILED DESCRIPTION

[0074] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0075] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0076] In the description of the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are real numbers. Unless otherwise specified, each reaction or operation step may be performed in sequence or not. Preferably, the reaction method of the present invention is performed in sequence.

[0077] If no specific techniques or conditions are specified in the following examples, the techniques or conditions described in the literature in the art or the product instructions are used. All reagents or instruments without manufacturer specified are conventional products that can be purchased commercially.

[0078] Example 1

[0079] This embodiment provides a composite structure negative electrode current collector, the current collector substrate is copper foil, oxygen-containing SP 2 The hybrid carbon material is reduced graphene oxide (rGO), and the adhesive is 3-glycidyloxypropylmethyldiethoxysilane (3-GPTS or γ-GPTS).

[0080] The preparation steps are:

[0081] (1) Add 12 mL of anhydrous methanol and 2 g / L of glycerol to 100 mL of ultrapure water, mix well, and adjust the pH to 4.5 with acetic acid, marked as solution I;

[0082] (2) Prepare 10 mL of a mixed solution of γ-GPTS and anhydrous methanol (3 mL γ-GPTS + 7 mL anhydrous methanol) in a volume ratio of 3:7, labeled as solution II;

[0083] (3) Take 90 mL of solution I, slowly add 10 mL of solution II, and stir at room temperature for 4 h to form a stable silanol solution (the volume fraction of γ-GPTS is 3%);

[0084] (4) rGO was placed in pure water and ultrasonically dispersed until uniform, and then added to the silanol solution and stirred for 2 hours to form a silanol-modified rGO aqueous solution, which was labeled as γ-GPTS-rGO solution;

[0085] (5) After the fresh negative electrode current collector (circular copper foil) was degreased and impurized, it was immersed in a γ-GPTS-rGO solution at a solution temperature of 30°C for 30 minutes, and then irradiated with infrared light to cure it, thereby obtaining a composite structure negative electrode current collector (labeled as γ-GPTS-rGO@Cu material).

[0086] Example 2

[0087] The difference from Example 1 is that the oxygen-containing group SP 2The hybrid carbon material is multi-walled carbon nanotubes (CNT), and the prepared composite structure negative electrode current collector is marked as γ-GPTS-CNT@Cu material.

[0088] The rest is the same as Example 1 and will not be described again here.

[0089] Example 3

[0090] The difference from Example 1 is that the adhesive is 3-aminopropyltriethoxysilane (3-APTS or γ-APTS), and the prepared composite structure negative electrode current collector is marked as γ-APTS-rGO@Cu material.

[0091] The rest is the same as Example 1 and will not be described again here.

[0092] Example 4

[0093] The difference from Example 1 is that in step (2), 10 mL of a mixed solution of γ-GPTS and anhydrous methanol (2 mL γ-GPTS + 8 mL anhydrous methanol) is prepared in a volume ratio of 2:8, and the volume fraction of γ-GPTS is 2%.

[0094] The rest is the same as Example 1 and will not be described again here.

[0095] Example 5

[0096] The difference from Example 1 is that in step (2), 10 mL of a mixed solution of γ-GPTS and anhydrous methanol (4 mL γ-GPTS + 6 mL anhydrous methanol) is prepared in a volume ratio of 4:6, and the volume fraction of γ-GPTS is 4%.

[0097] The rest is the same as Example 1 and will not be described again here.

[0098] Example 6

[0099] The difference from Example 1 is that in step (2), 10 mL of a mixed solution of γ-GPTS and anhydrous methanol (5 mL γ-GPTS+5 mL anhydrous methanol) is prepared in a volume ratio of 5:5, and the volume fraction of γ-GPTS is 5%.

[0100] The rest is the same as Example 1 and will not be described again here.

[0101] Example 7

[0102] The difference from Example 1 is that in step (5), the γ-GPTS-rGO solution with a solution temperature of 10° C. is immersed.

[0103] The rest is the same as Example 1 and will not be described again here.

[0104] Example 8

[0105] The difference from Example 1 is that in step (5), the γ-GPTS-rGO solution with a solution temperature of 20° C. is immersed.

[0106] The rest is the same as Example 1 and will not be described again here.

[0107] Example 9

[0108] The difference from Example 1 is that in step (5), the γ-GPTS-rGO solution with a solution temperature of 25° C. is immersed.

[0109] The rest is the same as Example 1 and will not be described again here.

[0110] Example 10

[0111] The difference from Example 1 is that in step (5), the γ-GPTS-rGO solution with a solution temperature of 40° C. is immersed.

[0112] The rest is the same as Example 1 and will not be described again here.

[0113] Embodiment 11

[0114] The difference from Example 1 is that in step (5), the immersion time in the γ-GPTS-rGO solution is 10 minutes.

[0115] The rest is the same as Example 1 and will not be described again here.

[0116] Example 12

[0117] The difference from Example 1 is that in step (5), the immersion time in the γ-GPTS-rGO solution is 20 minutes.

[0118] The rest is the same as Example 1 and will not be described again here.

[0119] Example 13

[0120] The difference from Example 1 is that in step (5), the immersion time in the γ-GPTS-rGO solution is 40 minutes.

[0121] The rest is the same as Example 1 and will not be described again here.

[0122] Embodiment 14

[0123] This embodiment provides a soft-pack cylindrical battery cell, which is prepared using the γ-GPTS-rGO@Cu current collector prepared in Example 1. The negative electrode current collector substrate is a high-strength double-sided smooth substrate copper foil with a thickness of 6 to 8 μm, and the negative electrode active material compaction ratio ranges from 1.4 to 1.5; the positive electrode current collector is an aluminum foil with a thickness of 10 to 12 μm, and the positive electrode active material compaction ratio is 3.75 to 3.85; an 8 to 10 μm oil-based diaphragm is used, and a winding structure with a centrally placed pole ear is used to prepare a soft-pack cylindrical battery cell, and the electrolyte uses a ratio of 1 mol / L LiPF6 and EC:DEC:EMC=1:1:1, and the fully charged 4.25V system is recorded as the finished battery cell A1.

[0124] Figure 3 Shown is a schematic diagram of the structure of the finished battery cell.

[0125] Embodiment 15

[0126] This embodiment provides a soft-pack laminated battery cell, which is prepared using the γ-GPTS-rGO@Cu current collector prepared in Example 1. The negative electrode current collector substrate is a high-strength double-sided smooth substrate copper foil with a thickness of 8 to 10 μm, and the negative electrode active material compaction ratio ranges from 1.35 to 1.45; the positive electrode current collector is an aluminum foil with a thickness of 14 to 16 μm, and the positive electrode active material compaction ratio is 3.55 to 3.65; a 12 to 14 μm oil-based diaphragm is used, the number of positive and negative single pieces is between 10 and 15 pcs, the electrolyte uses 1 mol / L LiPF6+0.02 mol / L LiODFP, and EC:DEC:EMC=1:1:1, and 0.5 to 2.0% EP is added, and the fully charged 4.2V system is recorded as the finished battery cell B1.

[0127] Example 16

[0128] This embodiment provides a battery pack, which uses the finished battery cell prepared in Example 15, uses 4 single battery cells, and adopts a 3-in-1 parallel connection to form a battery pack, which is recorded as battery pack C1.

[0129] Comparative Example 1

[0130] This embodiment provides a composite structure negative electrode current collector, the current collector substrate is copper foil, oxygen-containing SP 2 The hybrid carbon material is reduced graphene oxide (rGO) and does not contain a binder.

[0131] The preparation steps are:

[0132] (1) Add 12 mL of anhydrous methanol and 2 g / L of glycerol to 100 mL of ultrapure water, mix well, and adjust the pH to 4.5 with acetic acid, marked as solution I;

[0133] (2) placing rGO in pure water and ultrasonically dispersing it until it is uniform, then adding it to solution I and ultrasonically dispersing it until it is uniform, to form an rGO aqueous solution;

[0134] (3) After the fresh negative electrode current collector (circular copper foil) was degreased and impurity-free, it was immersed in an rGO aqueous solution at a solution temperature of 30°C for 30 minutes, and then photocured by infrared light to obtain a composite structure negative electrode current collector (marked as rGO@Cu material).

[0135] Comparative Example 2

[0136] This embodiment provides a soft-pack cylindrical battery cell, which is prepared using the rGO@Cu current collector prepared in Comparative Example 1. The negative electrode current collector substrate is a high-strength double-sided smooth substrate copper foil with a thickness of 6 to 8 μm, and the negative electrode active material compaction ratio ranges from 1.4 to 1.5; the positive electrode current collector is an aluminum foil with a thickness of 10 to 12 μm, and the positive electrode active material compaction ratio is 3.75 to 3.85; an 8 to 10 μm oil-based diaphragm is used, and a winding structure with a centrally placed pole ear is used to prepare a soft-pack cylindrical battery cell, and the electrolyte uses 1 mol / L LiPF6 and EC:DEC:EMC=1:1:1 ratio, and the fully charged 4.25V system is recorded as the finished battery cell A2.

[0137] Comparative Example 3

[0138] This embodiment provides a soft-pack laminated battery cell, which is prepared using the rGO@Cu current collector prepared in Comparative Example 1. The negative current collector substrate is a high-strength double-sided smooth substrate copper foil with a thickness of 8 to 10 μm, and the negative active material compaction ratio ranges from 1.35 to 1.45; the positive current collector is an aluminum foil with a thickness of 14 to 16 μm, and the positive active material compaction ratio is 3.55 to 3.65; a 12 to 14 μm oil-based diaphragm is used, the number of positive and negative single pieces is between 10 and 15 pcs, the electrolyte uses 1 mol / L LiPF6 + 0.02 mol / L LiODFP, and EC: DEC: EMC = 1:1:1, and 0.5 to 2.0% EP is added, and the fully charged 4.2V system is recorded as the finished battery cell B2.

[0139] Comparative Example 4

[0140] This embodiment provides a battery pack, which uses the finished battery cell prepared in Comparative Example 3, uses 4 single battery cells, and adopts a 3-in-1 parallel connection to form a battery pack, which is recorded as battery pack C2.

[0141] Comparative Example 5

[0142] This embodiment provides a soft-pack cylindrical battery cell, which is prepared using conventional copper foil as a current collector. The negative electrode current collector substrate is a high-strength double-sided smooth copper foil with a thickness of 6 to 8 μm, and the negative electrode active material compaction ratio ranges from 1.4 to 1.5; the positive electrode current collector is an aluminum foil with a thickness of 10 to 12 μm, and the positive electrode active material compaction ratio is 3.75 to 3.85; an 8 to 10 μm oil-based diaphragm is used, and a winding structure with a centrally placed pole ear is used to prepare a soft-pack cylindrical battery cell, and the electrolyte uses 1 mol / L LiPF6 and EC:DEC:EMC=1:1:1 ratio, and the fully charged 4.25V system is recorded as the finished battery cell A3.

[0143] Comparative Example 6

[0144] This embodiment provides a soft-pack laminated battery cell, which is prepared using conventional copper foil as a current collector. The negative electrode current collector substrate is a high-strength double-sided smooth base copper foil with a thickness of 8 to 10 μm, and the negative electrode active material compaction ratio ranges from 1.35 to 1.45; the positive electrode current collector is an aluminum foil with a thickness of 14 to 16 μm, and the positive electrode active material compaction ratio is 3.55 to 3.65; a 12 to 14 μm oil-based diaphragm is used, the number of positive and negative single pieces is between 10 and 15 pcs, the electrolyte uses 1 mol / L LiPF6 + 0.02 mol / L LiODFP, and EC: DEC: EMC = 1:1:1, and 0.5 to 2.0% EP is added, and the fully charged 4.2V system is recorded as the finished battery cell B3.

[0145] Comparative Example 7

[0146] This embodiment provides a battery pack, which uses the finished battery cell prepared in Comparative Example 6, uses 4 single battery cells, and adopts a 3-in-1 parallel connection to form a battery pack, which is recorded as battery pack C3.

[0147] Test Example 1

[0148] In order to visually verify the thermal conductivity of the prepared materials more intuitively, an infrared thermal imager is used to characterize each sample and compare the thermal images at different temperatures. The method is: place the sample material on a resistance furnace for single-sided heating, the temperature window is 25°C to 150°C, and obtain thermal images of the heat dissipation surface at intervals of 30 seconds. Due to the different materials, their thermal conductivity coefficients are also different.

[0149] The following samples were tested respectively: Sample I was an untreated positive electrode current collector (conventional disc aluminum foil), Sample II was an untreated negative electrode current collector (conventional disc copper foil), Sample III was the unmodified rGO@Cu material prepared in Comparative Example 1, and Sample IV was the modified γ-GPTS-rGO@Cu material prepared in Example 1.

[0150] The test results are as follows Figure 4As can be seen from the figure, as the temperature increases, the colors of the four materials gradually become lighter and brighter. At the same temperature, comparing the colors of the four materials, the color of γ-GPTS-rGO@Cu is lighter than the other three materials, indicating that γ-GPTS-rGO@Cu has the best thermal conductivity.

[0151] Test Example 2

[0152] In order to test the effect of the volume fraction of γ-GPTS in the silanol aqueous solution on the thermal conductivity of the negative electrode current collector, the thermal conductivity of the γ-GPTS-rGO@Cu materials prepared in Example 1 and Examples 4-6 was tested (the volume fraction of γ-GPTS was 3%, 2%, 4% and 5% respectively). The method is: the thermal diffusion coefficients of the four groups of materials were tested using a laser thermal conductivity meter, and the test temperature ranged from 25°C to 150°C.

[0153] The test results are as follows Figure 5 As can be seen from the figure, when the volume fraction is 3%, the thermal diffusion coefficient of the γ-GPTS-rGO@Cu material prepared by the silanol aqueous solution is the best.

[0154] Test Example 3

[0155] In order to test the effect of the temperature of the γ-GPTS-rGO solution in which the current collector matrix is ​​immersed on the thermal conductivity of the negative electrode current collector, the thermal conductivity of the γ-GPTS-rGO@Cu materials prepared in Example 1 and Examples 7-10 was tested (the temperature of the γ-GPTS-rGO solution in which the current collector matrix was immersed was 30°C, 10°C, 20°C, 25°C, and 40°C, respectively). The method is: the thermal diffusion coefficients of the five groups of materials were tested using a laser thermal conductivity meter, and the test temperature ranged from 50°C to 150°C.

[0156] The test results are as follows Figure 6 As can be seen from the figure, when the temperature of the γ-GPTS-rGO solution is 30°C, the thermal conductivity of the prepared γ-GPTS-rGO@Cu material is the best.

[0157] Test Example 4

[0158] In order to test the effect of the time for which the current collector matrix is ​​immersed in the γ-GPTS-rGO solution on the thermal conductivity of the negative electrode current collector, the thermal conductivity of the γ-GPTS-rGO@Cu materials prepared in Example 1 and Examples 11-13 was tested (the time for which the current collector matrix was immersed in the γ-GPTS-rGO solution was 30 min, 10 min, 20 min, and 40 min, respectively). The method is: the thermal diffusion coefficients of the four groups of materials were tested using a laser thermal conductivity meter, and the test temperature ranged from 25°C to 150°C.

[0159] The test results are as follows Figure 7 As can be seen from the figure, when the immersion time is 30 min, the thermal conductivity of the prepared γ-GPTS-rGO@Cu material is the best.

[0160] Test Example 5

[0161] The finished battery cell A1 prepared in Example 14, the finished battery cell A2 prepared in Comparative Example 2, and the finished battery cell A3 prepared in Comparative Example 5 were placed in a room temperature environment of 25°C, and discharged at the same time and rate at 100% SOC state, with the discharge rate of 1C discharge for 30min, 2C discharge for 20min, and 5C discharge for 5min. At the same time, the temperature of the Al tab area of ​​the battery cell, the middle temperature of the battery body, and the temperature of the Ni tab area were recorded. The data are shown in Tables 1-3 below:

[0162] Table 1 Test results of finished battery cell A1

[0163] Finished battery cell A1 Al ear area Battery body middle area Ni ear area Cell surface temperature before test 25℃ 25℃ 25℃ Surface temperature after 1C discharge 26.1℃ 26.2℃ 26.2℃ Surface temperature after 2C discharge 28.4℃ 28.3℃ 28.4℃ Surface temperature after 5C discharge 34.7℃ 34.5℃ 34.6℃

[0164] Table 2 Test results of finished battery cell A2

[0165] Finished battery cell A2 Al ear area Battery body middle area Ni ear area Cell surface temperature before test 25℃ 25℃ 25℃ Surface temperature after 1C discharge 26.1℃ 26.0℃ 26.2℃ Surface temperature after 2C discharge 28.1℃ 27.8℃ 28.0℃ Surface temperature after 5C discharge 35.8℃ 33.6℃ 35.7℃

[0166] Table 3 Test results of finished battery cell A3

[0167] Finished battery cell A3 Al ear area Battery body middle area Ni ear area Cell surface temperature before test 25℃ 25℃ 25℃ Surface temperature after 1C discharge 26.2℃ 25.9℃ 26.0℃ Surface temperature after 2C discharge 28.9℃ 27.1℃ 28.1℃ Surface temperature after 5C discharge 35.5℃ 32.5℃ 34.4℃

[0168] From the above results, it can be seen that under low-rate discharge conditions, there is no significant difference in the surface temperature of the three groups of finished battery cells. When the battery cell is discharged under 5C high-rate conditions, the surface temperature distribution of the finished battery cell A1 is the most uniform and the temperature is relatively low. The results prove that rGO is bridged to the copper matrix through γ-GPTS, effectively transferring heat quickly and evenly to various parts of the battery cell, preventing local overheating from causing battery cell failure.

[0169] Test Example 6

[0170] When the battery cell is charged at a high rate or even overcharged, the battery cell will also produce local overheating, leading to thermal runaway. The finished battery cell A1 prepared in Example 14, the finished battery cell A2 prepared in Comparative Example 2, and the finished battery cell A3 prepared in Comparative Example 5 were charged at 3.6C constant current and constant voltage at 4.25V for 420 minutes. The temperature between the Al tab and the main body of the battery cell and the Ni tab was recorded, and the data are shown in Table 4:

[0171] Table 4

[0172]

[0173]

[0174] From the above results, it can be seen that under the condition of continuous high-rate full-charge overcharging, the surface temperature distribution of the finished battery cell A1 is the most uniform, which effectively prevents local overheating from causing thermal runaway of the battery cell.

[0175] Test Example 7

[0176] When the battery cell is discharged in a low temperature environment, the internal resistance increases due to the low electrochemical kinetics, more battery cell energy is lost in the form of Joule heat, and due to the different current densities, the temperature inside the battery cell is quite different, resulting in a decrease in the battery cell discharge capacity ratio and a safety risk. The finished battery cell A1 prepared in Example 14, the finished battery cell A2 prepared in Comparative Example 2, and the finished battery cell A3 prepared in Comparative Example 5 were first used to record the capacity of the three groups of batteries discharged from 100% SOC to 0% SOC at 1C in a room temperature environment of 25°C, and the 1C discharge capacity ratios of the three groups of batteries were recorded in an environment set to -20°C, -10°C, and 0°C. The data is shown in Table 5:

[0177] Table 5

[0178] Battery group -20℃ Capacity Ratio -10℃ Capacity Ratio 0℃ Capacity Ratio Finished battery cell A1 80.3% 88.4% 94.3% Finished battery cell A2 72.7% 82.9% 91.5% Finished battery cell A3 70.3% 81.0% 89.6%

[0179] The above results show that in a low temperature environment, the discharge capacity ratio of the A1 group battery cells is higher. This can be attributed to the fact that Joule heat can be transferred to the internal structure of the battery cell more quickly. The rapid increase in temperature can reduce the internal impedance, thereby reducing the capacity loss.

[0180] Test Case 8

[0181] For cylindrical wound cells with a single-pole lug in the middle, the discharge rate is usually high at 5C, and the internal heat concentration phenomenon is still low for high-rate laminated cells. By charging and discharging laminated cells at high rates for a short time, the heating and heat transfer phenomena of the cells can be more clearly observed.

[0182] The finished battery cell B1 prepared in Example 15, the finished battery cell B2 prepared in Comparative Example 3, and the finished battery cell B3 prepared in Comparative Example 6 were placed in a room temperature environment of 25°C, and discharged at the same time and rate at 100% SOC state, with the discharge rate being 5C discharge for 10 min, 8C discharge for 5 min, and 10C discharge for 5 min. At the same time, the temperature of the head of the battery body, the middle temperature of the battery body, and the temperature of the tail of the body were recorded. The data are shown in Tables 6-8:

[0183] Table 6 Test results of finished battery cell B1

[0184]

[0185]

[0186] Table 7 Test results of finished battery cell B2

[0187] Finished battery cell B2 Battery cell head area Battery body middle area Battery cell tail area Cell surface temperature before test 25℃ 25℃ 25℃ Surface temperature after 5C discharge 38.1℃ 37.7℃ 37.2℃ 8C surface temperature after discharge 49.8℃ 49.2℃ 48.9℃ Surface temperature after 10C discharge 58.4℃ 58.0℃ 57.3℃

[0188] Table 8 Test results of finished battery cell B3

[0189] Finished battery cell B2 Battery cell head area Battery body middle area Battery cell tail area Cell surface temperature before test 25℃ 25℃ 25℃ Surface temperature after 5C discharge 40.6℃ 38.6℃ 38.2℃ 8C surface temperature after discharge 51.1℃ 48.1℃ 47.5℃ Surface temperature after 10C discharge 60.8℃ 59.2℃ 58.4℃

[0190] From the above results, it can be seen that when the stacked cells are discharged at high rates of 5C, 8C and 10C, the cells in group B1 using γ-GPTS-rGO@Cu as the current collector can effectively transfer heat to various parts of the cell quickly and evenly, preventing local overheating from causing cell failure.

[0191] Test Example 9

[0192] When the cell is charged at a high rate or even overcharged, the cell will also overheat locally, leading to thermal runaway. The finished cell B1 prepared in Example 15, the finished cell B2 prepared in Comparative Example 3, and the finished cell B3 prepared in Comparative Example 6 were charged at 4C constant current and constant voltage at 4.2V for 420 minutes. The temperature of the cell head, the middle of the cell, and the tail of the cell were recorded, and the data are shown in Table 9:

[0193] Table 9

[0194] Battery group Battery body head Battery body middle area Battery cell tail Finished battery cell B1 66.3℃ 66.1℃ 66.0℃ Finished battery cell B2 70.7℃ 69.8℃ 69.3℃ Finished battery cell B3 72.4℃ 71.5℃ 71.8℃

[0195] From the above results, it can be seen that under the condition of continuous high-rate full-charge overcharging, the surface temperature distribution of the finished battery cell B1 is the most uniform, which effectively prevents local overheating from causing thermal runaway of the battery cell.

[0196] Test Example 10

[0197] The finished battery cell B1 prepared in Example 15, the finished battery cell B2 prepared in Comparative Example 3, and the finished battery cell B3 prepared in Comparative Example 6 were tested. The capacity of the above three groups of batteries discharged from 100% SOC to 0% SOC at 1C was recorded in a room temperature environment of 25°C. The 5C discharge capacity ratio of the three groups of batteries was recorded in an environment with a temperature of -20°C, -10°C, and 0°C. The data is shown in Table 10:

[0198] Table 10

[0199] Battery group -20℃ Capacity Ratio -10℃ Capacity Ratio 0℃ Capacity Ratio Finished battery cell B1 82.7% 91.3% 96.9% Finished battery cell B2 75.7% 88.6% 93.3% Finished battery cell B3 72.3% 84.5% 91.8%

[0200] The above results show that in a low temperature environment, the discharge capacity ratio of the B1 group battery cells is higher, which can be attributed to the fact that the Joule heat can be transferred to the internal structure of the battery cell more quickly. The rapid increase in temperature can reduce the internal impedance, thereby reducing the capacity loss.

[0201] Test Example 11

[0202] Laminated high-rate cells are usually used in drones, etc. Laminated cell battery packs are usually used as power sources for drones and drones, and require ultra-high rate discharge in a short period of time. Therefore, the battery pack C1 prepared in Example 16, the battery pack C2 prepared in Comparative Example 4, and the battery pack C3 prepared in Comparative Example 7 were tested. In a 25°C environment, 15C discharge was performed for 2 minutes, and the temperature of the head, middle, and tail of the battery pack was recorded. The data is shown in Table 11:

[0203] Table 11

[0204] Battery Group Battery body head Battery body middle area Battery cell tail Battery Pack C1 62.5℃ 62.3℃ 62.3℃ Battery Pack C2 69.6℃ 67.7℃ 67.0℃ Battery Pack C3 71.0℃ 68.4℃ 67.6℃

[0205] From the above results, it can be seen that under the condition of ultra-high rate discharge in a short period of time, the surface temperature distribution of battery pack C1 is the most uniform, which effectively prevents local overheating from causing thermal runaway of the battery cell.

[0206] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A composite structure current collector, characterized in that: include: Current collector substrate, thermal conductive coating and current collector binder; The composition material of the thermal conductive coating includes SP containing oxygen groups. 2 Hybrid carbon materials; The current collector binder includes a silane coupling agent; The current collector binder bridges the current collector substrate and the thermal conductive coating through covalent bonds.

2. The composite structure current collector according to claim 1, characterized in that: The oxygen-containing group SP 2 The hybrid carbon material includes at least one of carbon nanotubes, graphene oxide, or reduced graphene oxide.

3. The composite structure current collector according to claim 1, characterized in that: The silane coupling agent includes at least one of 3-glycidyloxypropylmethyldiethoxysilane and 3-aminopropyltriethoxysilane.

4. The composite structure current collector according to claim 1, characterized in that: The composite structure current collector is a composite structure negative electrode current collector, and the current collector matrix includes at least one of copper foil and composite copper foil; And / or, the composite structure current collector is a composite structure positive electrode current collector, and the current collector matrix includes at least one of aluminum foil and composite aluminum foil; And / or, the thickness of the current collector matrix is ​​6 to 16 μm.

5. A method for preparing a composite structure current collector according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: adding a silane coupling agent into an alcohol solution, stirring and reacting for a predetermined time to generate a silanol solution; The oxygen-containing SP 2 After the hybrid carbon material is evenly dispersed in the solvent, the silanol solution is added and stirred for a predetermined reaction time to generate a silanol-modified SP 2 Hybrid carbon material solution; The current collector substrate is immersed in the silanol-modified SP at a predetermined temperature. 2 After reacting in the hybrid carbon material solution for a predetermined time of three, the solution is cured by light irradiation to obtain the composite structure current collector.

6. The method for preparing the composite structure current collector according to claim 5, characterized in that: In the silanol solution, the volume fraction of the silane coupling agent is 2% to 5%; And / or, the alcohol solution includes at least one of methanol, ethanol, and ethylene glycol; And / or, the predetermined time is 3 to 5 hours; And / or, the second predetermined time is 1 to 3 hours; And / or, the predetermined time three is 10 to 40 minutes; And / or, the predetermined temperature is 10-40°C; And / or, photocuring is performed using infrared light irradiation.

7. An electrode sheet, characterized in that: include: A composite structure current collector as described in any one of claims 1 to 4 or prepared by the preparation method as described in any one of claims 5 to 6, and an active material layer coated on at least one side of the surface of the composite structure current collector.

8. A battery cell, characterized in that: Comprising the electrode sheet as claimed in claim 7.

9. A lithium ion battery, characterized in that: Comprising the battery cell as claimed in claim 8.

10. Use of the lithium-ion battery according to claim 9 in an energy storage device, an electrical device or an electronic device.

Citation Information

Patent Citations

  • Copper-based grapehne polymer lithium battery negative electrode structure and production method thereof

    CN104538582A

  • Binder for silicon-based negative electrode of lithium ion battery, silicon-based negative electrode of lithium ion battery, preparation method of silicon-based negative electrode, and lithium ion battery

    CN110247017A

  • Copper foil having adhesive agent adhered thereto, copper-clad laminated plate, and wiring substrate

    CN110463363A

  • Method of modifying graphene oxide / copper foil composite through silane coupling agent, graphene oxide / copper foil composite and application thereof

    CN111996530A

  • Process for coating surface of copper foil for PCB (Printed Circuit Board) with silane coupling agent

    CN114107974A

Cited By

  • Battery, battery pack and electric equipment

    CN121355268A